Capturing a novel metastable polymorph of the anticancer drug gefitinib - Thorat, Shridhar H.; Patwadkar, Manjusha V.; Gonnade, Rajesh G.; Vaidhyanathan, R. (CrystEngComm, 2014)
Gefitinib, a life-extending anticancer drug, exhibits solvent-mediated conformational polymorphism to yield stable (form I) and novel metastable (form II) polymorphs. Crystal structure analysis revealed 3D isostructurality in the molecular organization of the polymorphs, and the metastable polymorph undergoes a crystal-to-crystal thermal phase transition to the stable polymorph.

Crystal structures of the pyrazinamide-p-aminobenzoic acid (1/1) cocrystal and the transamidation reaction product 4-(pyrazine-2-carboxamido)-benzoic acid in the molten state - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2015)
The synthesis of pharmaceutical cocrystals is a strategy to enhance the performance of active pharmaceutical ingredients (APIs) without affecting their therapeutic efficiency. The 1: 1 pharmaceutical cocrystal of the antituberculosis drug pyrazinamide (PZA) and the cocrystal former p-aminobenzoic acid (p-ABA), C7H7NO2- C5H5N3O, (1), was synthesized successfully and characterized by relevant solid-state characterization methods. The cocrystal crystallizes in the monoclinic space group P21/n containing one molecule of each component. Both molecules associate via intermolecular O-H center dot center dot center dot O and NH center dot center dot center dot O hydrogen bonds [O center dot center dot center dot O = 2.6102 (15)angstrom and O-H center dot center dot center dot O = 168.3 (19)degrees; N center dot center dot center dot O = 2.9259 (18) angstrom and N-H center dot center dot center dot O = 167.7 (16)degrees] to generate a dimeric acidamide synthon. Neighbouring dimers are linked centrosymmetrically through N-H center dot center dot center dot O interactions [N center dot center dot center dot O = 3.1201 (18) angstrom and N-H center dot center dot center dot O = 136.9 (14)degrees] to form a tetrameric assembly supplemented by C-H center dot center dot center dot N interactions [C center dot center dot center dot N = 3.5277 (19) angstrom and C-H center dot center dot center dot N = 147 degrees]. Linking of these tetrameric assemblies through N-H center dot center dot center dot O [N center dot center dot center dot O = 3.3026 (19) angstrom and N-H center dot center dot center dot O = 143.1 (17)degrees], NH center dot center dot center dot N [N center dot center dot center dot N = 3.221 (2) angstrom and N-H center dot center dot center dot N = 177.9 (17)degrees] and C-H center dot center dot center dot O [C center dot center dot center dot O = 3.5354 (18) angstrom and C-H center dot center dot center dot O = 152 degrees] interactions creates the twodimensional packing. Recrystallization of the cocrystals from the molten state revealed the formation of 4-(pyrazine-2-carboxamido) benzoic acid, C12H9N3O3, (2), through a transamidation reaction between PZA and p-ABA. Carboxamide (2) crystallizes in the triclinic space group P1 with one molecule in the asymmetric unit. Molecules of (2) form a centrosymmetric dimeric homosynthon through an acid-acid O-H center dot center dot center dot O hydrogen bond [O center dot center dot center dot O = 2.666 (3) angstrom and O-H center dot center dot center dot O = 178 (4) degrees]. Neighbouring assemblies are connected centrosymmetrically via a C-H center dot center dot center dot N interaction [C center dot center dot center dot N = 3.365 (3) angstrom and C-H center dot center dot center dot N = 142 degrees] engaging the pyrazine groups to generate a linear chain. Adjacent chains are connected loosely via C-H center dot center dot center dot O interactions [C center dot center dot center dot O = 3.212 (3) angstrom and CH center dot center dot center dot O = 149 degrees] to generate a two-dimensional sheet structure. Closely associated two-dimensional sheets in both compounds are stacked via aromatic pi-stacking interactions engaging the pyrazine and benzene rings to create a threedimensional multi-stack structure.
Keywords: acid-amide hetero-synthon; active pharmaceutical ingredient (API); cocrystal; crystal structure; hydrogen bonding; molten-state reaction; powder diffraction; transamidation reaction

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Furosemide cocrystals with pyridines: an interesting case of color cocrystal polymorphism - Sangtani, Ekta; Sahu, Sanjay Kumar; Thorat, Shridhar H.; Gawade, Rupesh L.; Jha, Kunal K.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2015)
Furosemide (FS), a loop diuretic drug commonly used for the treatment of hypertension and edema, exhibited color cocrystal polymorphism with coformer 4,4'-bipyridine (4BPY) in the stoichiometry 2:1, albeit both the API and the cocrystal former are colorless. Crystallization from ethanol, isopropanol, ethanol-water (v/v, 1/1) mixture, and acetonitrile yielded pale yellow (form II, thin needles) and orange (form 1II, blocks) cocrystals concomitantly. Needles appeared from solution within a day, while the blocks were obtained after 1-2 days from the same flask, indicating that yellow needles were formed faster and the orange blocks were perhaps formed under thermodynamic conditions. Form 1I cocrystals could also be produced from the variety of common solvents. Cocrystallization of FS with 2,2'-bipyridine (2BPY) and 4-aminopyridine (4AP) gave colorless cocrystals 2 and 3, respectively, and did not exhibit polymorphism. The single-crystal X-ray structures, powder X-ray diffraction, photophysical characterization, differential scanning calorimetry, hot stage microscopy studies, and density functional theory (DFT) calculations provide insight into the structure property relationship. The common structural features observed in all of the structures is the formation of sandwich motifs comprising FS and pyridines through pi-stacking interactions. These motifs are linked differently through hydrogen bonding interactions in all three directions. The significant color difference between the two cocrystals dimorphs could be attributed to the different pi-stacking patterns and hydrogen bonding interactions between molecules of FS and 4BPY in their cocrystal structures. Investigation on the origin of the color difference using DFT calculations revealed the decrease in HOMO-LUMO gap for form 1II cocrystals (orange) compared to form 1I crystals (light yellow). The crystal-to-crystal thermal transformation of form 1I crystals to form 1II crystals of 1 suggests the role of pi-stacking assemblies in driving the self-assembly.

Novel one-pot multi-component synthesis of 3,3 `-disubstituted oxindole and spirooxindole scaffolds via Sn-catalyzed C(sp(3))-H functionalization of azaarenes by sequential Knoevenagel-Michael-cyclization reaction - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek Abdul Rashid (RSC Advances, 2015)
Sn-catalyzed C(sp(3))-H bond functionalization of 2-methyl azaarenes/2-(azaaryl)methanes has been achieved for the first time in a one-pot multi-component reaction with isatin and active methylene compounds via tandem sequential Knoevenagel-Michael-intramolecular C-N cyclization. This strategy provides new cost-effective access to potent and biologically/medicinally important spirooxindoles/3,3'-disubstituted 2-oxindoles in good to excellent yields.

Reaction of N-heterocyclic carbenes with chalcones leading to the synthesis of deoxy-breslow intermediates in their oxidized form - Bhunia, Anup; Thorat, Shridhar H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
The synthesis of deoxy-Breslow intermediates in their oxidized form has been developed via the reaction of N-heterocyclic carbenes (NHCs) with chalcones. Moreover, the initial tetrahedral adduct formed from the 1,4-addition of NHCs to chalcones is also isolated.

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Cu-Catalyzed iminative hydroolefination of unactivated alkynes en route to 4-imino-tetrahydropyridines and 4-aminopyridines - Kumar, Ravi; Thorat, Shridhar H.; Reddy, Maddi Sridhar (Chemical Communications, 2016)
A general method for synthesizing 4-imino tetrahydropyridine derivatives is achieved, from readily available beta-enaminones and sulfonyl azides, which comprises a sequential copper catalyzed ketenimine formation and its hitherto inaccessible intramolecular hydrovinylation. The products are shown as ready precursors for highly valuable 4-sulfonamidopyridine derivatives via DDQ mediated oxidation.

Impact of modular substitution on crystal packing: the tale of two ureas - Koshti, Vijay S.; Thorat, Shridhar H.; Gote, Ravindra P.; Chikkali, Samir H.; Gonnade, Rajesh G. (CrystEngComm, 2016)

Ultrahydrophobic fluorous metal-organic framework derived recyclable composite as apromising platform to tackle marine oil spills - Mukherjee, Soumya; Kansara, Ankit M.; Saha, Debasis; Gonnade, Rajesh; Mullangi, Dinesh; Manna, Biplab; Desai, Aamod V.; Thorat, Shridhar H.; Singh, Puyam S.; Mukherjee, Arnab; Ghosh, Sujit K. (Chemistry-A European Journal, 2016)
Derived from a strategically chosen hexafluorinated dicarboxylate linker aimed at the designed synthesis of a superhydrophobic metal-organic framework (MOF), the fluorine-rich nanospace of a water-stable MOF (UHMOF-100) exhibits excellent water-repellent features. It registered the highest water contact angle (approximate to 176 degrees) in the MOF domain, marking the first example of an ultrahydrophobic MOF. Various experimental and theoretical studies reinforce its distinc-tive water-repellent characteristics, and the conjugation of superoleophilicity and unparalleled hydrophobicity of a MOF material has been coherently exploited to achieve real-time oil/water separation in recyclable membrane form, with significant absorption capacity performance. This is also the first report of an oil/water separating fluorinated ultrahydrophobic MOF-based membrane material, with potential promise for tackling marine oil spillages.

Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction

Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles

X-ray crystal structures and anti-breast cancer property of 3-tert-butoxycarbonyl-2-arylthiazolidine-4-carboxylic acids - Jagtap, Rohidas M.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Khan, Ayesha A.; Pardeshi, Satish K. (New Journal of Chemistry, 2018)
Diastereomeric `2RS, 4R'-2-arylthiazolidine-4-carboxylic acids (ATCAs) were synthesized and their resolution to chiraly pure N-BOC derivatives was attempted by column chromatography. The absolute stereochemistry of the resolved compounds was ascertained by X-ray single crystal structures. Further application of the synthesized compounds was studied for their in vitro anti-breast cancer activity against MCF7 cell line using DOX as a standard by MTT assay method. Cell morphology analysis was carried out by fluorescence microscopy. The compounds containing `2S' absolute configuration in thiazolidine ring and presence of 2-NO2, 2,6-Cl groups on `2R'-aryl substituent showed significant antibreast cancer activity where some of the compounds were found to be more active than DOX in terms of induced apoptosis mode of MCF7 cell death.

Drug-drug cocrystals of anticancer drugs erlotinib-furosemide and gefitinib-mefenamic acid for alternative multi-drug treatment - George, Christy P.; Thorat, Shridhar H.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (Crystengcomm, 2020)
Drug-drug cocrystals of anticancer drugs erlotinib and gefitinib with furosemide and mefenamic acid, respectively, have been synthesized. The 1:1 erlotinib-furosemide cocrystal crystallizes in the monoclinic centrosymmetric P2(1)/n space group containing one molecule of each component in the asymmetric unit. In contrast the 1:1 gefitinib-mefenamic acid cocrystal hydrate belongs to the monoclinic centrosymmetric P2(1)/c space group comprising one molecule of both drugs along with one water molecule in the asymmetric unit. The solubility and dissolution rate study revealed higher solubility for BCS class II drugs, furosemide, and mefenamic acid, while the solubility and dissolution rate of erlotinib showed a significant reduction in the cocrystal salt. Conversely, the solubility of gefitinib didn't reveal a substantial decrease; however, the dissolution rate has been reduced in the cocrystal hydrate. Further, an attempt has been made to correlate the crystal structures of the erlotinib-furosemide and gefitinib-mefenamic acid cocrystals with their solubilities and dissolution rate.

Polymorphs and hydrates of the anticancer drug erlotinib: X-ray crystallography, phase transition and biopharmaceutical studies - Thorat, Shridhar H.; George, Christy P.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (CrystEngComm, 2021)
Erlotinib, a non-small cell lung cancer BCS class II drug, was found to occur as two polymorphs and two hydrates depending on the crystallization conditions. The monohydrate (form III), which has been reported in patents and publications, is the preferred crystalline phase from solution crystallization. The other forms (polymorphs, forms I and II, and a trihydrate, form IV) are solvent and condition-specific. Form I was exclusively and reproducibly obtained from dried non-polar solvents (viz. toluene, benzene, and xylene) using a solution crystallization method under controlled conditions. In contrast, form II was obtained by the rotary evaporation technique under reduced pressure from polar solvents (viz. dichloromethane, ethyl acetate, acetone, and acetonitrile). Slow evaporation from polar and non-polar solvents under open conditions yielded form III crystals, whereas evaporation from acetone-acetonitrile-water mixtures yielded form IV crystals. DSC and variable temperature PXRD studies revealed form I to be the most stable phase while the other solid forms displayed thermally induced polymorphic transitions into form I crystals. Further, form I and form III are found to be stable over the 30-90% RH range. Further, form I displayed solution-mediated transformation into form III (monohydrate) when left to stand in the mother liquor for a longer duration (1-2 days). Similarly, the unstable form IV crystals transformed into the stable form III crystals within 1-2 h when exposed to an open atmosphere. Fast crystallization from polar solvents using the rotary evaporation technique enabled us to capture the metastable polymorph, form II. Early separation of form I from its mother liquor prevented its solution-mediated transformation into the monohydrate, form III. The water activity study revealed that form III is the most preferred solid phase in the presence of water. Dissolution rate measurements showed that the rate of form II is almost comparable to that of the marketed erlotinib hydrochloride. In contrast, for the other forms, the dissolution profiles showed a considerable decrease. Although the crystal structures of form I and form III have been published previously, this manuscript gives a comprehensive overview of the free base solid forms of erlotinib, the phase transitions amongst them and their biopharmaceutical properties.